ANALISIS STRATEGI PEMBANGUNAN HUTAN KOTA (STUDI KASUS KAWASAN DANAU RAJA KABUPATEN INDRAGIRI HULU) - Rudi Formen; Sofyan Husain Siregar; Thamrin Thamrin (Jurnal Ilmu Lingkungan, 2012)
Area Raja Lake reside in strategic location that is gateway enter Town Rengat at the sametime Pekanbaru trajectory band. Wide of Area is 21,6 Ha, wide of Raja Lake 7,8 Ha.Development of Forest town in this area because representing RTH and have compact arealthat is coppice 0,8 Ha and Garden Lawn 1,5 Ha. In Area Raja Lake also there are historicbuilding that is Replica of Indragiri Palace, GOR, custom institute and custom house. Foresttown development in Area Raja Lake can function as conservation area, natural educationand ecotourism. Result of governmental perception analysis and society to town forestdevelopment in Area Raja Lake show good category that is with amount of score 4.680.Governmental perception and society do very well by the understanding of hitting RTH withscore 866, while understanding of hitting governmental policy of sub-province reside in atgood enough category with score 645. Result of Rank Spearmen correlation analysis togovernmental group and society group have positive correlation with rs value 0,001 < 0,337(critical boundary value 5%) its meaning of H0 accepted. Result of SWOT analysis todetermination of town forest development strategy is chosen of WO strategy namely byexploiting existing opportunity and weakness minimization had. As for WO strategy is theexistence of budget allocation support for the development of town forest, improving SDM toconduct research of exploration or push related parties to do research, and infrastructuredevelopment around Raja Lake.